Neonatal chest image quality addressed through training to enhance radiographer awareness - Hesta Friedrich-Nel; Belinda van der Merwe; Beatrix Kotzé (AOSIS, 2018)
Background: Diagnostic radiographers working in the neonatal intensive care unit primarily aim to produce an image of optimal quality using optimal exposure techniques without repeating exposures, to keep neonatal radiation dose to a minimum.   Objectives: The aim of the study was to determine whether radiographers were producing optimal quality chest images and, if not, whether additional training could contribute to reaching this goal in the Free State Province of South Africa.   Methods: Neonatal chest image quality was determined in the Neonatal Intensive Care Unit by using a checklist based on and compiled from published guidelines to evaluate the quality of 450 randomly-selected images. Thereafter, a training programme was designed, based on the evaluation criteria of the checklist and image quality areas identified. The training also referred to positioning techniques that should be applied to ensure optimal image quality. After presentation of the training, 450 newly-produced neonatal chest images were evaluated. These images were selected through purposive sampling as this evaluation only included images of participating radiographers who completed the training.   Results: Image quality that showed significant improvement included a reduction in electrocardiogram lines superimposed on chest anatomy, a tendency to centre closer to thoracic vertebra four, and visible four-sided collimation on images. Image quality areas with no significant enhancement were the absence of lead markers and radiation shielding.   Conclusion: The study has shown that a training programme has the potential to improve neonatal chest image quality.